Soul of a nation [videorecording (DVD)] - Jakubowicz, Jonathan, 1978-; Bennett, Naftali, 1972-; Olmert, Ehud, 1945- (Kino Lorber, 2025)
An unfiltered look at Israel's most perilous chapter in recent history, a period defined by internal divisions and external threats. Drawing on insights from Nobel laureates, Muslim leaders, peace activists, and other prominent figures, the film dismantles preconceived notions about one of the world's most scrutinized countries.